Economic growth and imperialism - Giacomo Corneo (Freie Universität Berlin, School of Business & Economics, 2024)
History shows militarily dominant states that pursue imperialism, relying on their might to extort resources from weaker states. Occasionally, the latter revolt and the dominant state suffers some casualties. This paper explores imperialism along steady-growth paths. If the dominant state maximizes domestic welfare, it should eventually abandon imperialism because its safety costs asymptotically overrun its material benefits. To shed light on diametrically opposed historical records, I propose a model of endogenous ideology and war bias in which the political elite cares about self-image. If that concern is strong enough, the political elite gradually identifies with its country's mission of hegemony and imperialism persists. It is first driven by material concerns and later by ideal ones. Despite its divergent preferences, the population of a dominant state generally has little interest to oppose imperialism.
urn:nbn:de:kobv:188-refubium-45706-5
Keywords: H8; N4; O0; Z1; 330; imperialism; long-run growth; value of life; self-image